Physiotherapy support for self-management of persisting musculoskeletal pain disorders - Ina Diener (South African Journal of Physiotherapy, 2021)
Background: Musculoskeletal pain (MSKP) is an extremely common pain disorder in almost all populations. Self-management (SM) support is a programme to prepare people to self-manage their health condition effectively, while maintaining quality of life. SM is a cost-effective and context-specific strategy to address the global public health burden.